Combination of the custom trays bleaching technique with the in-office bleaching and considerations for result maintenance - Débora MONTEIRO; Adriana VIEIRA; Cláudia MAGALHÃES; Nelson SILVA; Rodrigo ALBUQUERQUE (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT This study goal is to present a case report of tooth bleaching treatment with the combination of the custom tray and in-office techniques, and to discuss about the considerations for result maintenance. A treatment approach was planned involving exogenous bleaching with custom trays with 7.5% hydrogen peroxide, and in-office bleaching with 35% hydrogen peroxide. The in-office bleaching agent was applied in two 15-minute applications, without led light. The patient was instructed to use the custom trays only a day after, with one drop of the bleaching agent for each tooth space. After the application of the bleaching agent, the patient used the trays for 1 hour per day, continuously for 30 days, 15 days for each arch. Considering the executed treatment approach, we may conclude that when correctly indicated, tooth bleaching with the combination of the in-office and custom trays techniques can be an acceptable choice of treatment, capable of enhancing the smile esthetics with a simple technique that preserves the sound dental structure. The patient should be instructed for the maximum color preservation and esthetic result maintenance, and should be advised that retreatments may become necessary depending on the oral hygiene and frequence of coloured food and drinks intake.